2010
DOI: 10.1099/vir.0.022335-0
|View full text |Cite
|
Sign up to set email alerts
|

The helper-component protease transmission factor of tobacco etch potyvirus binds specifically to an aphid ribosomal protein homologous to the laminin receptor precursor

Abstract: Potyviruses are plant pathogens transmitted by aphids in a non-persistent manner. During transmission, the virus-encoded factor helper-component protease (HCPro) is presumed to act as a molecular bridge, mediating the reversible retention of virions to uncharacterized binding sites in the vector mouthparts. Whilst the predicted interaction between HCPro and the coat protein (CP) of virions has been confirmed experimentally, the characterization of putative HCPro-specific receptors in aphids has remained elusiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 66 publications
0
19
0
1
Order By: Relevance
“…However, a Myzus persicae protein (MpRPS2) with homology to a ribosomal protein has been shown to bind TEV HC-Pro but not to a mutant HC-Pro with a modified KITC domain (Fernández-Calvino et al, 2010) and four potential interacting Myzus persicae proteins were found for the HC-Pro of ZYMV (which like the HC-Pro factors of BCMV and BCMNV has a KLSC sequence) (Dombrovsky et al, 2007).…”
Section: Molecular Determinants Of Aphid-mediated Transmission and Homentioning
confidence: 98%
“…However, a Myzus persicae protein (MpRPS2) with homology to a ribosomal protein has been shown to bind TEV HC-Pro but not to a mutant HC-Pro with a modified KITC domain (Fernández-Calvino et al, 2010) and four potential interacting Myzus persicae proteins were found for the HC-Pro of ZYMV (which like the HC-Pro factors of BCMV and BCMNV has a KLSC sequence) (Dombrovsky et al, 2007).…”
Section: Molecular Determinants Of Aphid-mediated Transmission and Homentioning
confidence: 98%
“…Besides, HCpro is also a vector transmission helper factor, mediating the retention of virions to aphid mouthparts. In the process, RPS2, as the potential laminin receptor precursor, binds HCpro of TEV to assist virus transmission [91].…”
Section: Interaction Between Viral Proteins and Ribosomal Proteinsmentioning
confidence: 99%
“…Finally, other aspects that remain to be determined in order to better understand the role of HCPro in transmission include the stoichiometry and geometry of the reversible virion-HCPro-vector interactions, which seem to involve multimers of HCPro (Plisson et al, 2003;Ruiz-Ferrer et al, 2005), and the location of this factor at one end of the viral particles (Torrance et al, 2006). Curiously, the visualization of virions within insect stylets has only been attempted and achieved with potyviruses in a very reduced number of studies (Wang et al, 1996), and only a few attempts to discover the vector receptors have been pursued and communicated (Dombrovsky et al, 2007;Fern andez-Calvino et al, 2010). Thus, at this point, it is still uncertain whether the potyvirusspecific aphid receptor co-localizes or shares properties with the putative receptors of viruses from other families (Blanc et al, 2014;Uzest et al, 2007).…”
Section: Transmission-a Historical Overview Of Hcpro Discoverymentioning
confidence: 99%